Rhysacephala novacaledonica sp. nov. (Hymenoptera: Xiphydriidae), the first xiphydriid woodwasp from New Caledonia - Jennings, John T.; Austin, Andrew D.; Schiff, Nathan M. (Zootaxa, 2007)
Xiphydriid woodwasps have been very rarely collected in Australasia although they are widely distributed in the region. Species have been described from the Aru, Ambon and Buru Islands, Indonesia, eastern mainland Australia, Papua New Guinea, and New Zealand. Here Rhysacephala novacaledonica Jennings & Austin, sp. nov., is described, which is the first record of a xiphydriid woodwasp from New Caledonia. In addition, a key to genera for the region is presented, along with a discussion of the biology and distribution of the group in Australasia.